1985
DOI: 10.1128/iai.50.1.43-49.1985
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic properties of Campylobacter jejuni: assay and correlation with clinical manifestations

Abstract: The pathogenic properties of 20 strains of Campylobacter jejuni isolated from persons with clearly defined clinical manifestations were determined. Cell-free broth filtrates were examined for (i) enterotoxin production by Chinese hamster tissue culture assay and an enzyme-linked immunosorbent assay (ELISA) employing GM1 ganglioside and affinity-purified antiserum to Escherichia coli heat-labile toxin, (ii) cytotoxin production by Vero and HeLa cell tissue culture lines, and (iii) their ability to cause fluid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 56 publications
(59 reference statements)
2
43
0
Order By: Relevance
“…Occasionally, rounding of HEp-2 cells was observed during the 6-h infection period. Infection of HEp-2 cells with C. jejuni and C. coli strains has been reported to cause cytopathic effects as cell rounding, loss of adherence, and death after 24 to 48 h of incubation (24,38).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, rounding of HEp-2 cells was observed during the 6-h infection period. Infection of HEp-2 cells with C. jejuni and C. coli strains has been reported to cause cytopathic effects as cell rounding, loss of adherence, and death after 24 to 48 h of incubation (24,38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent pathogenicity studies showed that some diarrhoeal strains of C. jejuni produce a cytotoxin either singly or along with a cytotonic toxin [3]. Other phenomena attributed to the pathogenesis of C. jejuni are colonisation and invasion of gut mucosa [4][5][6][7][8][9]. The interplay of the various virulence determinants of the pathogen in the disease process is unclear, but bacteraemia, infiltration and destruction of gut epithelial cells resulting in bloody diarrhoea indicates that a cytolytic process plays a part.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been proposed that disease involves translocation of the bacterium across the intestinal epithelium, with resultant tissue damage and inflammation (31). This latter proposal is based upon examinations of rectal biopsy specimens from C. jejuni-infected patients and, more recently, by the demonstration of the ability of C. jejuni to bind to and enter cultured epithelial cells (1,2,7,9,16,17,19,21). Although the relevance of the internalization of C. jejuni by cultured epithelial cells to in vivo behavior is largely presumptive, some evidence does suggest that such in vitro models may be useful in the elucidation of pathogenic mechanisms associated with C. jejuni enteritis.…”
mentioning
confidence: 99%